Karang Taruna Skills Training in Management and Sustainability of Websites as Publication Media for Karanganyar Tourism Village - Suryaningtyas, Annis Azhar; Andarini, Rachmawati Yulia; Jalaluddin, Alif; Ayu, Putri Java Esya; Kustanto, Yoga; Pamungkas, Diaz Resnu (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
The importance of digital publication of tourism villages. In fact, Karanganyar village already has a publication media in the form of a website with the address www.karanganyarborobudur.com. The information presented includes activities, tourism potential, and village cultural attractions. However, this publication activity is still not optimal. There are three factors that become obstacles in the consistency of managing the Karanganyar Village website. First, there are limited human resource skills in managing, developing, and producing published content on the website. Then, there is still no sustainable organization of website management as a village publication media by a legitimate village government. Finally, there is no transparency in communication and coordination between villages and youth organizations in managing the website. Therefore, the publication of tourism potential and activities in Karanganyar Village has not been able to spread outside. The implementation phase of integrated community service activities in Karanganyar Village is carried out for two months. The series of activities are the implementation of situation analysis, planning, implementation, as well as evaluation and reporting. The result of holding PPMT activity period V is that Karanganyar villagers get additional soft skills, namely the ability to process websites, write news properly and correctly in accordance with a communicative news writing structure, and have a clear organizational structure for website admin managers.